Aplikasi Jadwal Pintar Berbasis Gamifikasi untuk Optimalkan Produktivitas Waktu bagi Mahasiswa - Ade Maulana; Ferik Bagas Wardana; Muhammad Iqbal Hanafri; Neng Linda Badratul Laela (Sekawan Institut, 2024)
Time productivity is a significant challenge for students in the digital age, where they often struggle to manage their time effectively, which can impact their academic performance and life balance. This study aims to develop and test a